Adaptation of cost-effectiveness analyses to a single country: the case of bariatric surgery for obesity and overweight (Swiss Medical Weekly, 2018)
OBJECTIVES The aims of this study were to (a) identify and assess the quality of reporting of published cost-effectiveness studies of bariatric surgery, (b) assess their transferability to Switzerland, and (c) adapt transferable cost-effectiveness results to Switzerland. METHODS A systematic literature search was performed in Medline, Embase and other databases. Two reviewers independently undertook screening, extraction, assessment of reporting quality utilising the Consolidated Health Economic Evaluation Reporting Standards, transferability, adaptation of cost data and recalculation of cost-effectiveness results. Cost data were adapted in three steps: correction for different levels of resource utilisation, for different prices of healthcare services and for change in costs over time. RESULTS Fifteen studies fulfilled criteria for adaptation of cost data to Switzerland. Four out of fifteen adapted studies with a long time-horizon for patients with a body mass index (BMI) >35kg/m2 indicated bariatric surgery to be a cost-saving (dominant) approach compared with conventional treatment. Other studies for patients with BMI >35kg/m2 showed cost-effective results, with incremental cost-effectiveness ratios (ICERs) below CHF 50,000 per quality adjusted life-year (QALY) gained. Two studies assessed cost-effectiveness for patients with BMI